Role of Thyroidectomy in Recurrent Laryngeal Carcinoma. (May 2022) - Brunet, Aina; Tornari, Chrysostomos; Ezebuiro, Akunnah; Kennedy, Robert; Connor, Steve E. J.; Oakley, Richard; Jeannon, Jean-Pierre; Arora, Asit; Rovira, Aleix; Simo, Ricard
Objective: Management of recurrent laryngeal cancer presents a major challenge, and salvage laryngectomy is complicated by previous oncologic treatments. Thyroidectomy as part of salvage laryngectomy adds a nonnegligible degree of morbidity. The purpose of this study is to assess the rate of thyroid gland invasion in patients undergoing salvage laryngectomy to determine relevant predictive factors. Study Design: Case series with chart review. Setting: Department of Otorhinolaryngology, Head and Neck Surgery, Guy's Hospital, London, United Kingdom. Methods: A retrospective review of patients undergoing salvage laryngectomy between 2009 and 2019 was undertaken. Preoperative cross-sectional imaging and histopathological analysis were performed to define evidence and predictors of thyroid gland invasion (TGI). Results: Fifty-one patients had salvage laryngectomy. Histological evidence of TGI was found in 4 patients (7.8%). No significant relationship was found between histological TGI and subsite of primary carcinoma, degree of differentiation, T staging, or radiological TGI. Preoperative computed tomography had a high negative predictive value for TGI. Conclusion: Thyroidectomy should be carefully considered in patients undergoing salvage laryngectomy, and its extent should be defined on an individual basis. Total thyroidectomy should not routinely be performed in salvage laryngectomy or pharyngolaryngectomy in patients with no preoperative radiological evidence of TGI on cross-sectional imaging, unless there is intraoperative evidence of TGI.